Marketing communication strategy for academic branding through educational content - Eugenius Kau Suni (Jurnal Mantik, 2024)
Academic Branding is a communication technique to promote the competitiveness of educational institutions. This study intends to investigate marketing communication techniques for academic branding through case studies in the Information Systems Department, Faculty of Engineering, Atma Jaya Catholic University of Indonesia. This research adopts a case study approach with the following stages: data collecting stage, data processing stage, stage of data analysis and interpretation, and reporting phase. The results of this investigation reveal that The marketing communication strategy of the Information System Study Program at the Faculty of Engineering, Universitas Katolik Indonesia Atma Jaya, through educational content, proves to be highly beneficial in academic branding, effectively capturing the interest of prospective students. The primary emphasis is crafting informative and engaging educational content highlighting the program's unique features and academic offerings, including the MBKM. This strategy aligns with the preferences of contemporary learners who seek personalized and relevant information